CD19-Targeted T Cells for Hematologic Malignancies: Clinical Experience to Date. Issue 6 (November 2015) - Davila, Marco L.; Sauter, Craig; Brentjens, Renier
Abstract : Abstract: Recently, immunotherapy for cancer has begun to garner traction with encouraging results in a number of malignancies. Included within this arena has been the genetic engineering of autologous T cells with chimeric antigen receptors (CARs) against tumor target. The majority of this experience has included the use of CAR T cells directed against CD19 for B-cell hematologic malignancies. The most striking efficacy to date with CAR T cells directed against CD19 has been in relapsed and refractory B-cell acute lymphoblastic leukemia, with the overwhelming majority of patients experiencing complete remissions. In addition, single-center and largely early-phase studies have demonstrated responses in patients with varying histologic findings of relapsed and refractory B-cell non-Hodgkin lymphoma. The favorable response rates seen with this technology have been tempered by the high risk of toxicity, particularly in the form of cytokine-release syndrome and neurotoxicity. Agents such as tocilizumab and corticosteroids have been used to treat these toxicities. The current state of the science includes strategies to circumvent and treat toxicity, manufacturing, and study of later-generation CAR constructs with the intention of improving efficacy and development of CARs against other tumor targets for both hematologic and solid tumor malignancies. The observation of an early efficacy ensures further integration and development of this modality into future immunotherapeutic strategies for various cancers.